Migration Realism: Lessons from the Global Migration Crisis Anatomy of migration - Rahmon Ulmasov (Universitas Muhammadiyah Sidoarjo, 2019)
This paper makes analyses of the realism in global migration crisis. On this case, most of the view were stated in political views of the Central Asian region to global tendencies and issues overcome migration. Conclusions of the author shows analyses of contemporary conditions in the region while making suggestions to the future points.